One-step fabrication of robust superhydrophobic and superoleophilic surfaces with self-cleaning and oil/water separation function - Zhang, Zhi-hui; Wang, Hu-jun; Liang, Yun-hong; Li, Xiu-juan; Ren, Lu-quan; Cui, Zhen-quan; Luo, Cheng (Scientific reports, 2018)
Superhydrophobic surfaces have great potential for application in self-cleaning and oil/water separation. However, the large-scale practical applications of superhydrophobic coating surfaces are impeded by many factors, such as complicated fabrication processes, the use of fluorinated reagents and noxious organic solvents and poor mechanical stability. Herein, we describe the successful preparation of a fluorine-free multifunctional coating without noxious organic solvents that was brushed, dipped or sprayed onto glass slides and stainless-steel meshes as substrates. The obtained multifunctional superhydrophobic and superoleophilic surfaces (MSHOs) demonstrated self-cleaning abilities even when contaminated with or immersed in oil. The superhydrophobic surfaces were robust and maintained their water repellency after being scratched with a knife or abraded with sandpaper for 50 cycles. In addition, stainless-steel meshes sprayed with the coating quickly separated various oil/water mixtures with a high separation efficiency (>93%). Furthermore, the coated mesh maintained a high separation efficiency above 95% over 20 cycles of separation. This simple and effective strategy will inspire the large-scale fabrication of multifunctional surfaces for practical applications in self-cleaning and oil/water separation.